Choice Values of Development of Ecotourism Destination: The Case of Ban Nam Rad Community Forest, Khiri Rat Nikhom District, Surat Thani Province - Sriarkarin, Supasit; Uaareeleat, Apiwat; Janjumroon, Wichien; Muangsan, Preeyanan (Journal of Applied Economics and Management Strategy, 2023)
This paper aims to study the selective behavior of tourists on willingness to pay in the ecotourism development model of Ban Nam Rad Community Forest, Surat Thani Province. The model consists of developmental attributes of biodiversity conservation, tourist number control, natural interpretation sign boards system, promotion of seasonal tourism activities, and entrance fee. Data were obtained from interviews with 400 tourists. The study found that tourists gave the highest value of willingness to pay for the development of natural interpretation sign boards on the walking trails and on the canal side of boating at 18.95 baht per person per time. An integrated development policy for all attributes including the intensive levels of biodiversity conservation and tourist influx control and the developments of recreational activity and natural interpretation sign board system could increase the value of willingness to pay an entrance fee of up to 49.56 baht per person per time. Factors that influenced the differences in the level of willingness to pay for the development attributes were gender, age, education level, monthly income, number of visits, current residence, and recreational activities.